A New Nurse's First Days at the Bedside. (June 2016) - Anderson, Amanda
Abstract : This column is designed to help new nurses in their first year at the bedside—a time of insecurity, growth, and constant challenges—and to offer advice as they learn what it means to be a nurse. This first article addresses new nurses' anxiety at the bedside and offers practical tips on how to prepare for your first day. Abstract : In this initial installment of a new column for recent graduates, the author shares preparation tips for the first day on the job.